Ustawy w zakresie zapewniania bezpieczeństwa wewnętrznego (Internal Security Acts) w Indiach, Portugalii i Francji - Marczuk, Karina Paulina (Przegląd Strategiczny, 2016)
The article concerns Internal Security Acts in India, Portugal and France. These states had adopted such kind of laws due to various reasons and motives. In the paper a set of factors is identified which have influenced internal security rules in the above-mentioned states. The key assumption is that the crucial issue is the definition of internal security which is necessary if a state would like to build an internal security system. The definition might be included in an Internal Security Act. The basic question is how internal security is understood in India, Portugal and France. The article concludes with final conclusions. First, the Internal Security Acts adopted by various states are influenced by a set of factors occurring in these states. Secondly, usually the concept of internal security has been defined by an Internal Security Act (Portugal and France cases). Last but not least, the internal security is understood in a narrow way i.e. it is restricted to the issues of public order and public security (India and France cases).